Droplet Digital PCR for the Detection of Plasmodium falciparum DNA in Whole Blood and Serum: A Comparative Analysis with Other Molecular Methods - Pomari, Elena (Pathogens, 2020)
Background: The estimation of Plasmodium falciparum parasitaemia can vary according to the method used. Recently, droplet digital PCR (ddPCR) has been proposed as a promising approach in the molecular quantitation of Plasmodium, but its ability to predict the actual parasitaemia on clinical samples has not been largely investigated. Moreover, the possibility of applying the ddPCR-sensitive method to serum samples has never been explored. Methods: We used, for the first time, ddPCR on both blood and serum to detect the DNA of P. falciparum in 52 paired samples from 26 patients. ddPCR was compared with loop-mediated isothermal amplification (LAMP) and rtPCR. The correlation between the ddPCR results, microscopy, and clinical parameters was examined. Results: ddPCR and microscopy were found to be strongly correlated (ρ(26) = 0.83111, p < 0.0001) in blood. Samples deviating from the correlation were partially explained by clinical parameters. In serum samples, ddPCR revealed the best performance in detecting P. falciparum DNA, with 77% positive samples among malaria subjects. Conclusion: Absolute quantitation by ddPCR can be a flexible technique for Plasmodium detection, with potential application in the diagnosis of malaria. In particular, ddPCR is a powerful approach for Plasmodium DNA analysis on serum when blood samples are unavailable.